Viktimisasi Struktural terhadap Pengguna Jalan dalam Konteks Kemacetan Kota Besar - Sutresno, Nanang (Universitas Tribhuwana Tunggadewi, 2025)
The inequality in sources of livelihood between big cities and their surrounding areas has resulted in an unavoidable flow of urbanization. The density of commuter movement every day will cause detrimental traffic congestion. The author uses a victimology theory approach by focusing on the victim's perspective in describing the problems of public transportation management. This research was conducted using a literature study method through the collection and analysis of data and information originating from academic journals, news articles, books, laws and regulations, government and non-governmental organization reports, as well as related websites. The results of the study indicate that there is structural victimization of road users created by the government's reaction related to the business world in overcoming congestion and the reactions of road users themselves. The government needs to look for alternative public policies that can meet corporate interests as well as the broader public interest, so that victimization of road users caused by traffic congestion can be minimized.Ketimpangan sumber penghidupan antara kota besar dan daerah sekitarnya mengakibatkan arus urbanisasi tidak bisa dihindarkan. Kepadatan pergerakan kaum komuter setiap harinya akan menimbulkan kemacetan lalu lintas yang merugikan. Penulis menggunakan pendekatan teori viktimologi dengan memfokuskan sudut pandang korban dalam menguraikan permasalahan pengelolaan transportasi publik. Penelitian ini dilakukan dengan metode studi literatur melalui pengumpulan serta analisis data dan informasi yang berasal dari jurnal akademik, artikel berita, buku, aturan perundang-undangan, laporan pemerintah maupun organisasi non-pemerintah, serta situs web yang terkait dengan penelitian. Hasil penelitian menunjukkan adanya viktimisasi struktural terhadap pengguna jalan yang tercipta dari reaksi pemerintah terkait dengan dunia usaha dalam mengatasi kemacetan maupun reaksi pengguna jalan itu sendiri. Pemerintah perlu mencari alternatif kebijakan publik yang dapat memenuhi kepentingan korporasi sekaligus kepentingan umum yang lebih luas, sehingga viktimisasi pengguna jalan yang diakibatkan oleh kemacetan lalu lintas dapat diminimalisasi.